Pemanfaatan Kulit Buah Manggis Sebagai Bahan Campuran dalam Panganan Manyarakat Sebagai Upaya Penanganan Limbah Kulit Manggis di Daerah Desa Gegelang, Lombok Barat - Khairul Pahmi Rahmawati; Abdul Muin; Diah Miftahul Aini; Baiq Desy Ratnasri; Faelga Sara Rosiana (PT FORMOSA CENDEKIA GLOBAL, 2022)
This activity is presented to handle waste as well as to improve public health by utilizing medicinal raw materials that have not been used optimally by the community into food or beverages that are pleasant to consume. This service was carried out in Gegelang Village, Lingsar District, West Lombok, in collaboration with the local village PKK driving team. The target of this service is the village community, especially mothers who are the heart of the family who serve food in the middle of the family every day. This service was carried out in the early months of February 2022. Community service received a positive response from the community, as evidenced by a high level of satisfaction. Furthermore, this service activity succeeded in inviting the community to use mangosteen peel extract for food additives.